If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(0)+-2=-2
We simplify the equation to the form, which is simple to understand
4(0)+-2=-2
Reorder the terms in parentheses
+()+-2=-2
Remove unnecessary parentheses
+-2=-2
We move all terms containing to the left and all other terms to the right.
0=-2-0
We simplify left and right side of the equation.
0=-2
0=-2
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 10x-26=264 | | 3x-8x= | | 21b^2-114b-72=0 | | 87=5n-23 | | .12(18)+0.03x=0.06(24+x) | | 10x=264 | | 37=x+48 | | 18m^2-77m-18=0 | | 3(0)=-y+3 | | 3-8h=35 | | 13-x=-8 | | 3(-2)=-y+3 | | 8x^2-46xy+11y^2=0 | | 30-3x=2+x | | 2m^2+13m+10=0 | | 2m^2-10-4=4 | | .5x+12=27 | | 16x-3y=18 | | 12x^2+133x+11=0 | | 350-167+v=2v | | 68+2x-30=x+42 | | Y+(-8)=-23 | | 24-x=42 | | 4x+5=2(3x+25) | | 6x-2=2x-10 | | (3x+8)(8x+7)=0 | | y=-0.50*40+121 | | y=-0.50*30+121 | | y=-0.50*20+121 | | 2x+48=322 | | 119=6x+17 | | 1500x=20x |